2022
DOI: 10.3389/fnsyn.2022.826098
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicle Recycling and the Endolysosomal System: A Reappraisal of Form and Function

Abstract: The endolysosomal system is present in all cell types. Within these cells, it performs a series of essential roles, such as trafficking and sorting of membrane cargo, intracellular signaling, control of metabolism and degradation. A specific compartment within central neurons, called the presynapse, mediates inter-neuronal communication via the fusion of neurotransmitter-containing synaptic vesicles (SVs). The localized recycling of SVs and their organization into functional pools is widely assumed to be a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 233 publications
0
11
0
Order By: Relevance
“…A mechanism for distal recycling of presynaptic components would likely require a transport system involving intracellular vesicles or endosomes (Ivanova & Cousin, 2022). Rab11 is a small GTPase required for recycling endosome function (Ullrich et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanism for distal recycling of presynaptic components would likely require a transport system involving intracellular vesicles or endosomes (Ivanova & Cousin, 2022). Rab11 is a small GTPase required for recycling endosome function (Ullrich et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of abundant endocytic structures in remodeling DD axons and their dependence on UNC-8 which promotes presynaptic disassembly, suggested that SV components could be recycled by an ADBE-like mechanism for reassembly, in this case, to nascent presynaptic domains in dorsal DD neurites (Figure 1A) (Park et al, 2011). A mechanism for distal recycling of presynaptic components would likely require a transport system involving intracellular vesicles or endosomes (Ivanova & Cousin, 2022). Rab11 is a small GTPase required for recycling endosome function (Ullrich et al, 1996).…”
Section: Recycling Endosomes Function Downstream Of Unc-8 To Mediate ...mentioning
confidence: 95%
“…Consequently, the immune system represents the third counterpart of the combined neuroimmune system. [20] "Neurogenic" inflammation [18,21] Neuroendocrine Hypothalamus, pituitary gland, and peripheral endocrine glands (i.e., HPA axis on the whole) Endocrine gland cells NEC [11,22,23] General adaptation syndrome [16] Immune Primary, secondary, and tertiary organs Immune cells (lymphocytes and non-lymphoid immune cells) Immune cell-derived extracellular vesicles [24] Barrier epithelium's cells (ciliated, deuterosomal, goblet, club, basal, suprabasal, tuft cells, ionocytes, etc. [7,10] Innate immunity Pathways of adaptive immune responses Immune (allergen) tolerance [25,26]…”
Section: Combined Neuroimmune Systemmentioning
confidence: 99%
“…Local SV recycling at the presynapse is an essential process for the maintenance of neurotransmission ( Ceccarelli et al, 1973 ; Heuser and Reese, 1973 ). However, the exact molecular mechanisms underlying SV recycling are still not completely understood, especially in vivo (for review see Kokotos and Cousin, 2015 ; Watanabe and Boucrot, 2017 ; Chanaday et al, 2019 ; Ivanova and Cousin, 2022 ). Till date, four different, mutually non-exclusive mechanisms for synaptic endocytosis have been described.…”
Section: Introductionmentioning
confidence: 99%